LEVERAGING IDIOSYNCRATIC RISK TO SUPPORT SUSTAINABLE DEVELOPMENT GOALS (SDGS) AND ITS IMPACT ON ECONOMIC GROWTH AT ASEAN COUNTRIES - Asri, Marselinus; Tunjungsari, Hetty Karunia; Tongli, Bernadeth (International Journal of Application on Economics and Business, 2024)
This study investigates the dynamics between economic growth and key determinants, Sustainable Development Goals (SDGs) related to poverty reduction (SDG 1) and affordable clean energy (SDG 7), as well as Idiosyncratic Risk, in ASEAN countries. Utilizing regression analysis, the research uncovers intriguing insights into these relationships. The findings reveal a significant positive association between Idiosyncratic Risk and economic growth, indicating that higher levels of idiosyncratic risk are linked with greater economic activity and innovation. However, the analysis suggests that SDG 1 (No Poverty) initiatives do not directly impact economic growth within the model's framework, highlighting the need for further exploration of indirect effects. Additionally, the promotion of SDG 7 (Affordable Clean Energy) exhibits a statistically significant but negative relationship with economic growth, possibly due to initial investments in clean energy infrastructure. These findings underscore the complex interplay between sustainable development goals, idiosyncratic risk, and economic growth in the ASEAN region, offering valuable insights for policymakers and stakeholders aiming to foster inclusive and sustainable economic development.